Suicide and suicide attempts in children and adolescents in the child welfare system - Katz, Laurence Y. (Canadian Medical Association, 2011)
BACKGROUND: Few population studies have examined the psychiatric outcomes of children and adolescents in the child welfare system, and no studies have compared outcomes before and after entry into care. Our objective was to assess the relative rate (RR) of suicide, attempted suicide, admission to hospital and visits to physicians’ offices among children and adolescents in care compared with those not in care. We also examined these outcomes within the child welfare population before and after entry into care. METHODS: We used population-level data to identify children and adolescents 5 to 17 years of age who were in care in Manitoba for the first time between Apr. 1, 1997, and Mar. 31, 2006, and a comparison cohort not in care. We compared the two cohorts to obtain RRs for the specified outcomes. We also determined RRs within the child welfare population relative to the same population two years before entry into care. RESULTS: We identified 8279 children and adolescents in care for the first time and a comparison cohort of 353 050 children and adolescents not in care. Outcome rates were higher among those in care than in the comparison cohort for suicide (adjusted RR 3.54, 95% confidence interval [CI] 2.11–5.95), attempted suicide (adjusted RR 2.11, 95% CI 1.84–2.43) and all other outcomes. However, adjusted RRs for attempted suicide (RR 0.27, 95% CI 0.21–0.34), admissions to hospital and physician visits decreased after entry into care. INTERPRETATION: Children and adolescents in care were at greater risk of suicide and attempting suicide than those who were not in care. Rates of suicide attempts and hospital admissions within this population were highest before entry into care and decreased thereafter.